Visions of the Stars and Earth: The Images of Jean Coulthard - Colton, Glenn (Canadian University Music Review / Revue de musique des universités canadiennes, 2001)
Image Astrale (1981) and the companion piece Image Terrestre (1990) may be regarded as the defining works of Jean Coulthard's mature pianistic style. Both works feature idiomatic and, at times, virtuosic piano writing, a personal application of sonata form principles, a melodic style which vacillates between dramatic intensity and serene lyricism, and the neo-impressionistic evocation of contrasting images and moods through rich and varied harmonic colours. This article explores Coulthard's Images from both analytical and historical perspectives, assessing relevant style features and demonstrating the significance of the set within Coulthard's œuvre, Canadian music, and twentieth-century piano repertoire.